2023
DOI: 10.1038/s41598-022-26013-4
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the British agricultural revolution through the isotopic analysis of dated parchment

Abstract: Between the sixteenth and nineteenth century, British agriculture underwent a ‘revolutionary’ transformation. Yet despite over a century of research and the recognised centrality of agricultural developments to industrialisation and population growth, the character or chronology of any ‘revolution’ during this period remains contentious. Enquiry has been hampered by the fragmented and locally specific nature of historic accounts and the broad dating of early-modern zooarchaeological assemblages. To address thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…With the exception of three pigs, all animals exhibited 𝛿 13 C coll , 𝛿 13 C carb and 𝛿 15 N values consistent with livestock raised in the British Isles grazing on C 3 forage and fodder crops. The substantial range in cattle and sheep 𝛿 15 N values (5.4‰ and 7.2‰, respectively) likely reflects the large geographical range from which livestock were drawn to feed the burgeoning industrial towns (Scola, 1992) and the diversity in environmental conditions and land management practices in these areas, particularly the intensity of manuring (Doherty et al, 2023). Elevated 𝛿 15 N values in some pigs and domestic fowl indicate a diet with a component of animal protein, typical of omnivores consuming human refuse (Halley & Rosvold, 2014; Hammond & O'Connor, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of three pigs, all animals exhibited 𝛿 13 C coll , 𝛿 13 C carb and 𝛿 15 N values consistent with livestock raised in the British Isles grazing on C 3 forage and fodder crops. The substantial range in cattle and sheep 𝛿 15 N values (5.4‰ and 7.2‰, respectively) likely reflects the large geographical range from which livestock were drawn to feed the burgeoning industrial towns (Scola, 1992) and the diversity in environmental conditions and land management practices in these areas, particularly the intensity of manuring (Doherty et al, 2023). Elevated 𝛿 15 N values in some pigs and domestic fowl indicate a diet with a component of animal protein, typical of omnivores consuming human refuse (Halley & Rosvold, 2014; Hammond & O'Connor, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In cases where there are elevated δ 13 C and δ 15 N values (corresponding to Functions 1 and 2 respectively in this case) in children under the age of 2, this may be interpreted to have resulted from breastfeeding (Beaumont et al, 2015), therefore all non-adults were excluded from the overall interpretation of a C 4 diet. Around to feed the burgeoning industrial towns (Scola, 1992) and the diversity in environmental conditions and land management practices in these areas, particularly the intensity of manuring (Doherty et al, 2023).…”
Section: Isotope Analysismentioning
confidence: 99%
“…Skin-based samples should have high gelatin yields because most of the sample weight is composed of collagen. While bone gelatin yields below 2-4% indicate that the bone gelatin is degraded(DeNiro and Weiner 1988; van Klinken 1999), previous tests of gelatinizing historical parchment show gelatin yields by mass ranging from 46.7-71.3%(Brock 2013) and 32.4-98.3%(Doherty et al 2023). Experimental results have also shown that contemporary unprocessed skin samples have average gelatin yields of 70%, slightly higher than the average 63% yield of parchment(Doherty et al 2021).…”
mentioning
confidence: 97%